2015
DOI: 10.1055/s-0034-1399243
|View full text |Cite
|
Sign up to set email alerts
|

Akute pharmakologische Therapieoptionen von ängstlicher Symptomatik bei Patienten mit Depression

Abstract: Patients with depression often also present symptoms of anxiety. First-line pharmacotherapy of comorbid symptoms of depression and anxiety is often a combination therapy of an antidepressant agent, which is combined with benzodiazepines. However, benzodiazepines pose the drawbacks of being associated with cognitive and motor impairments and hold a significant risk for dependence. For some patients, benzodiazepines are contraindicated or patients refuse to take them. Therefore, alternative therapy strategies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Retrieved publications also included a contraceptives interaction study [21] and a case report [22]. The remaining five publications were review articles from which no additional studies with Silexan in patients with subthreshold anxiety could be identified [14, 2326]. Searches performed in clinical trials registries also did not reveal any additional studies with Silexan performed in the indication of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Retrieved publications also included a contraceptives interaction study [21] and a case report [22]. The remaining five publications were review articles from which no additional studies with Silexan in patients with subthreshold anxiety could be identified [14, 2326]. Searches performed in clinical trials registries also did not reveal any additional studies with Silexan performed in the indication of interest.…”
Section: Methodsmentioning
confidence: 99%